2020
DOI: 10.3389/fpubh.2020.00180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education and Age on Metabolic Disorders

Abstract: Metabolic disorders, such as obesity, elevated blood pressure, dyslipidemias, insulin resistance, hyperglycemia, and hyperuricemia have all been identified as risk factors for an epidemic of important and widespread chronic-degenerative diseases, such as type 2 diabetes and cardiovascular disease, that constitute some of the world's most important public health challenges. Their increasing prevalence can be associated with an aging population and to lifestyles within an obesogenic environment. Taking education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 111 publications
4
31
2
1
Order By: Relevance
“…Our results indicated that metabolic multimorbidity was positively associated with older age, urban area, and health insurance. Consistent with other studies (35,36), the prevalence of metabolic multimorbidity increased with age, which can be attributed to the declining metabolic function during the aging process. Additionally, individuals living in urban areas are more likely to suffer from metabolic multimorbidity than those living in rural areas, which is in line with previous findings (30,37).…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicated that metabolic multimorbidity was positively associated with older age, urban area, and health insurance. Consistent with other studies (35,36), the prevalence of metabolic multimorbidity increased with age, which can be attributed to the declining metabolic function during the aging process. Additionally, individuals living in urban areas are more likely to suffer from metabolic multimorbidity than those living in rural areas, which is in line with previous findings (30,37).…”
Section: Discussionsupporting
confidence: 90%
“…The rising incidence of metabolic diseases, namely, obesity, metabolic syndrome, or type II diabetes mellitus, is one of the main social challenges ahead now and in the coming years [ 1 ]. These diseases are closely related to dietary habits, in general, and particularly associated with the consumption of sugar-sweetened beverages [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, the physiological compensatory systems that maintain homeostasis become worn down due to the cumulative impact of metabolic insults, transitioning from healthy to maladaptive states that precede disease onset ( Stephens et al, 2020 ). An already existing medical notion of this system-wide progression of states before the overt onset of disease is metabolic syndrome (MetS), whose prevalence increases strongly with age ( Hildrum et al, 2007 ) and unhealthy lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…As metabolic health is an emergent property, arising from the interaction of multiple physiological systems over time, the framework of complexity provides the means for a whole-system analysis ( Lusis et al, 2008 ; Haring et al, 2012 ; Sun et al, 2012 ), rather than a reductionist variable-by-variable approach. In previous work ( Stephens et al, 2020 ), we considered how aging was an important driver of metabolic change across a wide variety of metabolic biomarkers (anthropometric, fasting blood test and vital signs measurements), considering each one individually and noting a substantial degree of heterogeneity as to the impact of aging across them. In contrast, in the present study, we have used Complex Inference Networks ( Stephens et al, 2009 , 2018 ) of these biomarkers as a means to give a more holistic, systems-biology perspective in order to demonstrate how the changes in the coupling between regulated variables and those regulatory systems that try to maintain homeostasis lead to metabolic health changes over a lifetime.…”
Section: Introductionmentioning
confidence: 99%